PERFORMANCE EVALUATION OF SOFTWARE DEVELOPMENT PROJECT TEAM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The necessity of finding the connection between the planning, decision making, actions and results create project management interest to an evaluation of the project team performance. By analyzing the team performance, determining successful projects and assessing results, members of such project will have the necessary information to avoid failures, to monitor the progress, to compare similar projects and move to defined goals. The objective of this paper is to provide guidelines for evaluation of the project team performance in the software development project. This paper summarizes measures for evaluation of the team performance, an evaluation objectives and it benefits as well as factors that may have an influence on the team performance. Demonstration example of the guideline usage has been provided.